Effect of dew-irrigation on seed yield and physiological traits in chickpea - Saiede Sargol Hosseini‎; Hassan Heidari; Mohammad Eghbal Ghobadi; Iraj Nosratti (Journal of Applied Research in Water and Wastewater)
Water shortage leads researchers and farmers to find new water resources. Water production from air vapor is a new idea. A field experiment was designed to determine the effect of dew-irrigation on chickpea seed yield and physiological traits. The field experiment included three treatments (dew-irrigation, conventional irrigation, and dryland farming). Irrigation treatments had no significant effect on chlorophyll a, chlorophyll b, total chlorophyll, chlorophyll a/b, relative water content, seed yield and yield attributing traits, and morphological traits. The mean comparison showed that dew-irrigation had higher stomatal conductance, chlorophyll fluorescence parameter (FV/FM), and photosynthesis performance index compared to dryland farming (62, 16, and 245% increase, respectively). Conventional irrigation had a higher photosynthesis performance index compared to dryland farming. Some plant physiological traits such as stomatal conductance clearly showed the positive effect of dew-irrigation on plant growth. The study of different levels of energy for water production can be informative in the next experiments.